Triple threat - Bond, Gwenda (Bond, Gwenda. Lois Lane., 2017)
Lois Lane has a stable home, a dream job, and incredible best friends. The one thing her life is missing is a boyfriend, but if all goes well she will soon meet her online crush, SmallvilleGuy, when he visits Metropolis and start something more than friendship with him. However, before they can meet, Lois will have to stop a mad scientist and a trio of rampaging mutant teens, as well as find a way to protect the elusive flying man from federal investigation.